THE COMPARISON OF POLITENESS STRATEGIES USED BY MALE AND FEMALE MAIN CHARACTER IN MUNDRUCZÓ’S PIECES OF A WOMAN MOVIE - Yustikarani, Margaretha Intan; Pradipta, Bramantya (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research discusses the comparison of politeness strategies used by male and female main characters in the Pieces of a Woman’s movie (2020), focusing on how gender and power affect their language choices. The study uses Brown and Levinson’s (1987) politeness theory as the main theory with Sara Mills’s (2003) gender and politeness theory as the support theory and applies a descriptive qualitative method. A total of 428 utterances from the two main characters, Sean (male) and Martha (female), were analyzed and grouped into four types of politeness strategies: Bald on Record, Positive Politeness, Negative Politenes, and Off the Record. The results show that Sean used all four strategies, with Positive Politeness being the most common (121 uterances), followed by Bald on Record (46), Of the Record 22), and Negative Politeness (10). This means Sean often tries to build closeness and familiarity but also speaks directly when needed. Martha, on the other hand, produced 229 utterances, with Positive Politeness being the most frequent (161), showing she focuses more on emotional closeness and maintaining good relationships. She also used Off the Record (28), Bald on Record (31), and Negative Politeness (9). Martha’s choices show a more careful and emotionally sensitive way of speaking. Overall, the study finds that gender and power influence how people choose politeness strategies. The female character used more polite and indirect language, while male character combined closeness to gather empathy to get what he wants.